Nucleotides: an updated review of their concentration in breast milk - Hodgkinson, Alison; Wall, Clare; Wang, Wendan; Szeto, Ignatius M.; Ye, Wenhui; Day, Li (Nutrition research (New York, N.Y.), 2022)
Our knowledge about the complexity of human milk, in particular fatty acid, protein, and oligosaccharide profiles, has increased considerably in recent years. However, little attention has been paid to nucleotides, which account for ∼2% to 5% of the nonprotein nitrogen fraction of breast milk and provide important cellular and metabolism functions for the infant. We examined literature published in the past 25 years to provide an updated review of concentrations of nucleotides in breast milk across lactational stages in mothers around the world. The free mononucleotides found in highest concentrations in breast milk are, from highest to lowest in the order of cytidine 5′-monophosphate, uridine 5′-monophosphate, and adenosine 5′-monophosphate, guanosine 5′-monophosphate, and inosine 5′-monophosphate. Levels of nucleotides varied considerably amongst individual mothers and with stage of lactation. They could be further influenced by time of day and season and the mother's diet. Levels of free nucleotides varied between studies undertaken in different regions; however, in studies that measured total potentially available nucleotides levels, regional differences were not apparent. Some studies report higher amounts in colostrum and transition milk compared with mature milk, whereas other studies report the converse. Recently, clinical studies showed that there are benefits to supplement nucleotides in infant formula. Although comparing data in the literature remains a challenge because of different milk collection methodologies and measurement protocols used by different studies, the information may provide insights for designing of formula products for infant at different stages of development. [Display omitted]